2020
DOI: 10.1128/msystems.00986-20
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Systematic Functional Profiling Unveils Citral Targeting Antibiotic Resistance, Antioxidant Defense, and Biofilm-Associated Two-Component Systems of Acinetobacter baumannii To Encumber Biofilm and Virulence Traits

Abstract: Acinetobacter baumannii has been reported as a multidrug-resistant bacterium due to biofilms and antimicrobial resistance mechanisms. Hence, novel therapeutic strategies are necessary to overcome A. baumannii infections. This study revealed that citral at 200 μg/ml attenuated A. baumannii biofilms by up to 90% without affecting viability. Furthermore, microscopic analyses and in vitro assays confirmed the antibiofilm efficacy of citral. The global effect of citral on A. baumannii was evaluated by proteomic, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In recent years, A. baumannii has aroused widespread concern due to its virulence and persistence ( 1 ). The pathogenicity of A. baumannii is mediated mainly by several vital virulence factors that are associated with motility ( 2 ) and adhesion to and invasion of host cells ( 3 ) that collectively enable A. baumannii to successfully infect its host. Regarding drug resistance, A. baumannii is also considered an emerging health threat due to its multidrug-resistant characteristics ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, A. baumannii has aroused widespread concern due to its virulence and persistence ( 1 ). The pathogenicity of A. baumannii is mediated mainly by several vital virulence factors that are associated with motility ( 2 ) and adhesion to and invasion of host cells ( 3 ) that collectively enable A. baumannii to successfully infect its host. Regarding drug resistance, A. baumannii is also considered an emerging health threat due to its multidrug-resistant characteristics ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it was reported that various derivatives of phenolic compounds control ExoS expression via the interference of a TCS called GacS-GacA [25]. Additionally, in a global analysis based on omics, it was found that citral (essential oil) acts through several mechanisms to reduce virulence (QS-regulated factors, type II and type IV secretion systems) of A. baumannii [28].…”
Section: Discussionmentioning
confidence: 99%
“…In most studies evaluating anti-virulence activity with substances of plant origin, inhibition of pigment biosynthesis regulated by QS, such as violacein in Chromobacterium violaceum and pyocyanin in P. aeruginosa, has been commonly used [17][18][19]. To a lesser extent, other relevant targets such as type III secretion systems (T3SSs) [20,21], key enzymes [22], toxins [23], or two-component systems, among others, have also been evaluated [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Citral, a mixture of monoterpene aldehydes from plants, has no bactericidal effect but a strong detoxification effect with naturally safe annon-toxic, which can reduce the toxicity of A. baumannii biofilm by 90%. Citral is targeted to various mechanisms, such as biofilm formation, antibiotic resistance, antioxidant defense, iron acquisition, and type II and type IV secretion systems enhance the sensitivity of A. baumannii to the host innate immune system and reactive oxygen species (ROS) (Selvaraj et al, 2020 ).…”
Section: Adjuvantmentioning
confidence: 99%